Hak-hak Perempuan dalam Pernikahan Perspektif Tafsir Sufistik: Analisis terhadap Penafsiran Al-Alusi dan ‘Abd al-Qadir al-Jilani - Lilik Ummi Kaltsum (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
The major problem discussed in this article is the presence of domestic violence conducted by husbands towards their wives in their marriages. Several verses of the Qur’an have been used to legitimize these arrogant actions. Using religious texts and culture of patriarchy, domestic violence seems to persist. This article discusses the interpretation of some verses of the Qur’an, especially the mystical interpretation, which is related to the rights of wives in marriage. Two mystical interpretations are the case of the study, i.e., Ruh al-Ma‘ani of al-Alusi and al-Fawatih al-Ilahiyya of al-Jilani. This article describes analytically and critically explores the ideas of al-Jilani and al-Alusi about women’s rights in Islam.